(1195) Subject Guide to the Institute of National Planning - سميحة مشرف (معهد التخطيط القومى, 2026)
ملخص This Subject Guide is a comprehensive bibliographic and documentation reference with the objective of organizing and indexing the Institute’s scientific and research output produced between January 1967 and December 1976. The guide was developed to provide researchers, experts, and planning professionals with a systematic tool for identifying and accessing the studies, reports, and memoranda issued by the Institute during this important period. The publication adopts an alphabetical and subject-based classification system, grouping memoranda under major thematic headings covering a broad spectrum of development and planning fields. These include national accounting, administration, agrarian reform, agricultural economics, agricultural marketing, agricultural planning and development, statistics, banking, international trade, electronic computers, consumption, costs, credit, cotton industry and textiles, econometrics, economic development, economic growth, economic integration, economic models, and other subjects closely related to national development and planning. In addition, the guide contains an author index identifying memorandum numbers and corresponding pages, with special notation for works written in Arabic and translated titles to facilitate access for non-Arabic-speaking researchers. It also includes title and subject indexes arranged alphabetically to enhance information retrieval and bibliographic access. The document represents an important archival and scholarly resource for tracing the evolution of planning thought, economic research, and development studies in Egypt during a decade characterized by significant economic and social transformation. Furthermore, it reflects the research priorities of the Institute and its contribution to national development planning. As a cumulative bibliographic record, the guide serves as a valuable historical source that preserves the intellectual output of the Institute, supports future academic investigations, and strengthens documentation and information services for researchers, planners, and policy-makers. يُعد هذا الدليل الموضوعي مرجعًا توثيقيًا وببليوجرافيًا شاملً بهدف حصر وتنظيم الإنتاج العلمي والبحثي الصادر عن المعهد خلال الفترة من يناير 1967 حتى ديسمبر 1976. ويأتي هذا العمل استجابةً للحاجة إلى توفير أداة علمية تسهل على الباحثين والخبراء والعاملين في مجالات التخطيط والتنمية الوصول إلى الدراسات والمذكرات العلمية التي أُنجزت داخل المعهد. اعتمد الدليل منهجًا تصنيفيًا قائمًا على الفهرسة الموضوعية والأبجدية، حيث جُمعت المذكرات تحت رؤوس موضوعات رئيسية تغطي نطاقًا واسعًا من مجالات التخطيط الاقتصادي والاجتماعي والتنمية، مثل المحاسبة القومية، والإدارة، والإصلاح الزراعي، والاقتصاد الزراعي، والتسويق الزراعي، والتخطيط الزراعي، والإحصاء، والبنوك، والتجارة الدولية، والحاسبات الإلكترونية، والاستهلاك، والتكاليف، والائتمان، وصناعة القطن، والقياس الاقتصادي، والتنمية الاقتصادية، والنمو الاقتصادي، والتكامل الاقتصادي، والنماذج الاقتصادية وغيرها من الموضوعات المرتبطة بقضايا التنمية والتخطيط. كما يتضمن الدليل كشافًا للمؤلفين يوضح أرقام المذكرات وصفحاتها، مع الإشارة إلى الأعمال المكتوبة باللغة العربية وترجمة عناوينها لتيسير الاستفادة منها من قبل الباحثين غير الناطقين بالعربية، إضافة إلى كشاف للعناوين وكشاف موضوعي مرتب أبجديًا ييسر عملية الاسترجاع والوصول إلى المعلومات. وتمثل هذه الوثيقة أداة مرجعية مهمة لتتبع تطور الفكر التخطيطي والبحثي في مصر خلال عقد شهد تحولات اقتصادية واجتماعية بارزة، كما تعكس اهتمامات الباحثين والمؤسسات الأكاديمية بقضايا التنمية الوطنية وأساليب التخطيط الحديثة. وتبرز أهمية الدليل في كونه مصدرًا تاريخيًا ومعرفيًا يساهم في دعم الدراسات اللاحقة، وتيسير الوصول إلى التراث البحثي المتراكم لمعهد التخطيط القومي، وتعزيز كفاءة خدمات المعلومات والتوثيق للباحثين وصناع السياسات.